L’intégration d’une composante d’expérience communautaire à la formation médicale en milieu francophone minoritaire - Beauchamp, Jacinthe; Daigle, Monique; Boucher, Micheline (Reflets, 2014)

L’attraction organisationnelle et les valeurs des jeunes : le cas du personnel infirmier en milieu hospitalier - Bouchard, Pier; Vézina, Sylvain (Minorités linguistiques et société, 2015)
La prestation de services de santé de qualité aux communautés francophones soulève la question de la disponibilité des ressources humaines, des jeunes professionnels en particulier. Ainsi, les gestionnaires des établissements de santé doivent élaborer des stratégies de recrutement/rétention qui tiennent compte des aspirations et des valeurs des jeunes. À cet égard, nous présentons ici les résultats d’une enquête menée auprès d’infirmières et de gestionnaires d’un important établissement de santé francophone du Nouveau-Brunswick. Ces résultats nous amènent à proposer des pistes d’action susceptibles de favoriser l’engagement des jeunes professionnels qui deviendront les ambassadeurs de services de santé en français de qualité. Mots-clés : services de santé en français, valeurs et aspirations des jeunes, recrutement, rétention, infirmières, gestion des ressources humaines, hôpital, leadership transformationnel

Coup d’œil sur la recherche : Implantation d’un programme de formation à l’offre active de services en français auprès des futurs professionnels de la santé et des services sociaux dans une université canadienne. - Consortium national de formation en santé; van Kemenade, Solange (2022)

Nursing students’ well-being: A comparison of two canadian nursing programs in different linguistic contexts - de Moissac, Danielle; Gueye, Ndeye Rokhaya; Vigier, Darcelle; Waddell, Candice; Graham, Jan Marie (Linguistic Minorities and Society, 2022)
Nursing programs are highly competitive and stressful environments; nursing educators are looking for ways to mitigate the negative consequences of demanding training programs. This article explores and compares the mental health status and sociodemographic and personal characteristics that influence the psychological distress of nursing and non-nursing students learning in either official language of Canada. An online and paper survey was administered during class time to 990 students, 186 of whom were in an undergraduate nursing program in one of two postsecondary institutions in Manitoba, Canada. Findings demonstrate that students in nursing programs are more likely to report poor mental health than students in other undergraduate programs and that nursing students in the French-language institution report poorer mental health outcomes as compared to nursing students in the English-language institution. Life satisfaction and high self-esteem are positively associated with well-being, whereas age, gender, and learning in a second language are risk factors contributing to anxiety. Keywords: mental health, risk behaviour, nursing students, linguistic minority, risk factors

The Forgotten: The Challenges Faced by Francophone Nursing Candidates following the Introduction of the NCLEX-RN in Canada - Lalonde, Michelle (Nursing Leadership, 2019)
In 2015, the traditional paper-and-pencil entry-to-practice exam in Canada was replaced by a computer-adaptive testing exam, the American National Council Licensure Examination for Registered Nurses (NCLEX-RN). As there are two official languages in Canada - English and French - the NCLEX-RN was translated to French. Although initially the pass rates for anglophone writers with the NCLEX-RN were lower than with the previous Canadian licensing exam, their pass rates have now increased. By contrast, francophone writers have continued to have lower pass rates, and a decreasing number of candidates are choosing to write the exam in French. A lack of access to French language preparatory resources is being reported by francophone graduates as one of the contributing factors. Canadian nursing regulators report that they are not responsible for ensuring that candidates have access to preparatory materials. However, given the bilingual culture and heritage in Canada, there is a responsibility to ensure equitable access to preparatory resources to ensure success on the licensing exam. This paper raises alarm about the decreasing number of francophone graduates writing the NCLEX-RN in French and the ongoing delivery of safe, quality nursing care to francophone patients by nurses proficient in the French language.

Les Effets Potentiels de la Version Française du NCLEX-RN® sur le Choix de la Langue de Formation d'Étudiantes Infirmières Francophones en Situation Minoritaire. - Lalonde, Michelle; Chartrand, Julie; Vanderspank- Wright, Brandi; McGillis Hall, Linda; Gosselin-Bélanger, Amélie; Fullum, Jessica Adèle (Quality Advancement in Nursing Education - Avancées en formation infirmière, 2020)
Background: Since the introduction of the new entry to practice exam, the NCLEX-RN®, there has been a very low success rate among Francophone nursing students living in minority situations. In addition, there has been a drop in the number of candidates who choose to write the exam in French. These results are of great concern in terms of the quality and sustainability of French language health services in French language minority communities in Canada. Objectives: The purpose of this article is to present the results of a study exploring the experiences of students enrolled in an entry level nursing program in French in terms of their decision-making regarding: 1) the choice of the language of the nursing program in which they were enrolled, 2) the language in which they chose to write the NCLEX-RN®, 3) their interest in working in a Francophone context, 4) their general knowledge of the new entry to practice exam, and 5) information sources on the NCLEX-RN©. Methodology: A sequential mixed methods design using surveys with multiple-choice and open-ended questions was used to conduct this study. Descriptive analyzes, as well thematic and content analysis, were used to analyze the data. Results: 51 students from a francophone graduating cohort participated in this study. The majority of the participants expected to write the NCLEX-RN® in English; the media attention on the French version of the exam influenced their decision. Four main themes were highlighted : 1) Choice of language of student based on their first language, 2) Three main factors that influence the choice of the language in which they write the NCLEX-RN®, 3) Colleagues and media as sources of information on the NCLEX-RN®, and 4) Importance and pride of studying in French. Conclusion: The results of this project shed light on the factors that influence francophone students' decision-making regarding the choice of language for the exam and the reasons why graduating students would choose to study in French again or not. , Contexte : Un très faible taux de réussite a été remarqué chez les étudiantes infirmières francophones en situation minoritaire ainsi qu’une chute du nombre de candidates qui choisissent de passer en français le nouvel examen d’autorisation, le NCLEX-RN®, qui a été introduit en 2015. Ces données sont préoccupantes s’agissant de la qualité et de la pérennité des services de santé en français dans les régions linguistiques minoritaires au Canada. Objectifs : Le but de cet article est de présenter les résultats concernant les expériences des étudiantes inscrites dans un programme de formation initiale en sciences infirmières en français sur leur prise de décision quant à : 1) la langue du programme auquel elles se sont inscrites, 2) la langue dans laquelle elles ont choisi de passer le NCLEX-RN®, 3) leur intérêt à travailler dans un contexte francophone, 4) leurs connaissances générales relatives au nouvel examen d’autorisation et 5) les sources d’information sur le NCLEX-RN®. Méthodologie : Un devis de recherche mixte séquentiel a été retenu comportant l’utilisation de questionnaires. Des analyses descriptives et des analyses thématiques et de contenu ont été effectuées. Résultats : 51 étudiantes de la cohorte francophone ont participé à cette étude. La majorité des participantes comptaient passer le NCLEX-RN® en anglais; l’intérêt médiatique porté à la version française de l’examen a eu une influence sur leur décision. Quatre grands thèmes ont été mis en évidence à partir des questions à court développement du questionnaire : 1) langue maternelle choisie comme langue de formation, 2) trois principaux facteurs qui influencent le choix de la langue pour le NCLEX-RN®, 3) collègues et médias comme sources d’information sur le NCLEX-RN®, et 4) importance et fierté d'étudier en français. Conclusion : Les résultats de ce projet ont mis en évidence les facteurs qui influencent la prise de décision des étudiants francophones quant au choix de la langue de l’examen et les raisons pour lesquelles les finissantes étudieraient à nouveau en français.

Improving the recruitment and retention of doctors by training medical students locally - Landry, Michel; Schofield, Aurel; Bordage, Rachel; Bélanger, Mathieu (Medical Education, 2011)
Context The global shortage of doctors is of concern. This is particularly true in French‐speaking regions of New Brunswick, Canada, where there is no medical school. Since 1981, francophone medical students from New Brunswick have been able to undertake part of their training in their province through an agreement with medical schools in another province. We studied the effects of frequency and length of exposure to the province of origin during medical training on the likelihood that a doctor will ever or currently practise medicine in that province. Methods A questionnaire was sent to 390 francophone doctors from New Brunswick to collect information on history of medical training and practice. Multivariate logistic regressions were used to identify whether exposure to New Brunswick during medical training at the undergraduate and postgraduate levels affects the likelihood of ever or currently practising in the province. Results A total of 263 doctors participated. Among family doctors, those with exposure to their province of origin in 1, 2, 3 or 4 years of undergraduate training were 2.5 (95% confidence interval [CI] 0.8–7.4), 2.5 (95% CI 0.7–8.6), 9.3 (95% CI 1.5–56.9) and 9.3 (95% CI 1.4–60.1) times more likely, respectively, to currently practise in New Brunswick than doctors who had experienced no exposure to the province during undergraduate training. Among specialty doctors, exposure to New Brunswick during undergraduate training had no effect on location of practice. Family and specialty doctors who had been exposed to New Brunswick during postgraduate residency were 5.9 (95% CI 2.3–14.9) and 3.2 (95% CI 0.9–11.6) times more likely, respectively, to practise in the province than doctors without postgraduate exposure. Conclusions Greater exposure to New Brunswick during medical training is associated with significantly better odds that doctors will be recruited to and retained in the province. Some effects are perceived for exposure during both undergraduate (most importantly in the final years) and postgraduate programmes.

La formation professionnelle en santé d'étudiantes issues des communautés d'immigrants francophones s'intégrant à la minorité francophone nationale au Canada - Laperrière, Hélène (Aporia, 2010)
Au Canada, plus spécifiquement dans la capitale nationale, il y a une mise-en-oeuvre considérable de programmes pour offrir une formation en français à la minorité francophone nationale. Toutefois, les observations actuelles dans la formation professionnelle en santé, clairement présentes en sciences infirmières, démontrent que les étudiants et les étudiantes francophones sont de plus en plus issus d'un sous-groupe formé de communautés immigrantes plus ou moins récentes. La formation en santé dans les programmes universitaires canadiens doit aujourd'hui relever le défi contemporain de former avec des connaissances théoriques plus ou moins uniformisées pour répondre aux compétences nationales de la majorité anglophone et de la minorité nationale francophone, tout en essayant de mieux comprendre les cultures d'origine de ses nouveaux étudiants francophones. Cet article présente la prise de conscience de cette nouvelle problématique durant un stage clinique en santé communautaire.

Expérience des étudiants francophones issus d’immigrations récentes lors de leur première année d’étude en sciences infirmières - Larocque, Sylvie; Lavoie, Anne. Marise; Muray, Kalum; Waja, Chamberline (Revue de la Diversité de la Recherche en Santé, 2021)
fs-ref-orig: Larocque, S., Lavoie, A. M., Muray, K. et Waja, C. (2021). Expérience des étudiants francophones issus d’immigrations récentes lors de leur première année d’étude en sciences infirmières. Revue de la Diversité de la Recherche en Santé, 4, 33-48. https://pubs.biblio.laurentian.ca/index.php/drhj-rdrs/Article de revue /view/324/287 fs-code-orig: Larocque-2021

Le défi de la formation universitaire des audiologistes et orthophonistes pouvant offrir des services aux francophones de l’Ontario - Lefebvre, Pascal; Marcoux, André (Éducation francophone en milieu minoritaire, 2011)
Cette étude avait pour but d’identifier les facteurs contribuant à la rétention des audiologistes et orthophonistes pouvant offrir des services auprès des francophones de l’Ontario. Une étude rétrospective comprenant des analyses descriptives et une régression logistique fut menée auprès de 192 finissants du Programme d’audiologie et d’orthophonie de l’Université d’Ottawa. Les résultats démontrent une relation significative entre le lieu de travail et quatre facteurs : le lieu de provenance de l’étudiant, la priorité du choix de l’université, la langue d’enseignement au baccalauréat, ainsi que le niveau de confiance à travailler en anglais. Les analyses démontrent également que le lieu de provenance peut fortement prédire à lui seul si un finissant du programme choisira l’Ontario comme lieu de travail. Des recommandations sont proposées concernant l’admission et la formation des étudiants de ce type de programme afin d’assurer une forte rétention de professionnels francophones en Ontario.

Socially responsible medical education: innovations and challenges in a minority setting - Schofield, Aurel; Bourgeois, Daniel (Medical Education, 2010)
Context Distributed medical education sites help train, recruit and retain doctors, notably in rural and isolated areas, by providing education and training in these areas and adapting their curriculum to meet the host community’s health needs. Objectives The Centre de Formation Médicale du Nouveau Brunswick (CFMNB; New Brunswick Medical Education Centre) was established by a partnership between two academic institutions, the Université de Sherbrooke (University of Sherbrooke), situated in the province of Quebec, and the Université de Moncton (University of Moncton), situated in the province of New Brunswick, in Canada. The CFMNB is specifically targeting a minority community (Acadians). Working to establish a high‐quality medical education programme, the CFMNB has also set community objectives to meet not only the health needs of this population, but also its social and economic needs. Methods This paper describes the overall objectives of this project, which are: to reduce the gap between community needs and academic institutional needs; to address ethno‐cultural and language differences in a defined minority population, and to develop collaboration between the partners involved, including government and community entities which are often perceived as operating in isolation from one another. We also describe why and how the CFMNB developed community‐focused objectives and the challenges that came with these innovations, and present lessons from the experience that may be relevant to other sites interested in the social responsibility of medical schools. Conclusions The CFMNB has produced interesting work and innovations in the field of social responsibility and has encountered many challenges. Continuing interaction between medical education, health research and health services to better address the needs of the population has been established. The information obtained by this process has been used to build a strategic plan for the CFMNB in order to ensure that it is socially responsive and has significant generalisable features.

Un modèle de création de simulation virtuelle en langue française pour le curriculum canadien du baccalauréat en sciences infirmières - Tyerman, Jane; Bailey, Liana (Revue Francophone Internationale de Recherche Infirmière, 2025)
Bien que le Canada soit un pays officiellement bilingue, il serait nécessaire d’augmenter de façon significative le nombre de ressources éducatives de bonne qualité en français, pour les étudiants en sciences infirmières. La simulation virtuelle est un outil pédagogique apprécié pour sa capacité d’être à la fois accessible, flexible et sécuritaire. Le but de cet article est de détailler le processus de création de simulations virtuelles en langue française utilisée pour le curriculum canadien du baccalauréat en sciences infirmières. Cet article propose un modèle en quatre étapes soutenant la création de simulations virtuelles en français : la rédaction/conversion, l’évaluation par les pairs, la revue finale et la publication. Le produit final est un référentiel d’outils pédagogiques permettant le renforcement de la formation des infirmières. Summary Although Canada is an officially bilingual country, there is still a need to significantly increase the number of good-quality, French-language educational resources for nursing students. Virtual simulation is a pedagogical tool that is appreciated for its ability to be accessible, flexible and safe. The aim of this article is to detail the process used to create French-language virtual simulations for the Canadian baccalaureate nursing curriculum. This article proposes a four-stage model supporting the creation of French-language virtual simulations: writing/conversion, peer review, final review, and publication. The final product is a repository of pedagogical tools to reinforce nursing education.